Novo meio espalhador (TiO2@Sílica) para um laser aleatório - Silva Júnior, Valdeci Mestre da (2014)
Interest in disordered media has increased in recent years due to its promising applications in solar collectors, photocatalyzers, random lasers and other novel optical devices. In this work, we introduce a new novel core–shell scattering medium for a random laser composed of core-shell TiO2@Silica nanoparticles. The TiO2 particles having an average diameter of 410 nm were coated with a silica shell via of the Stober method using tetraethyl-orthosilicate (TEOS) as the silica precursor. Two kinds of random laser samples were studied, both containing a concentration of 1x10-4 M of Rhodamine 6G (R6G), one smaple with TiO2 scattering nanoparticles and the other with TiO2@Silica coated with a layer of silica. With these samples, the laser action and photodegradation process of the dye and the TiO2 particles we investigated. In addtion, an absorption-emission saturation phenomenon was observed in the random laser composed by TiO2@Silica Nps. A new method or parameter (fraction of absorbed pumping) has been introduced, which opens a new avenue to characterize and study the scattering media. The random lasers composed of core-shell TiO2@Silica showed higher efficiency, lower laser threshold and long photobleaching lifetime. These improvements were attributed to the effects of optical colloidal stability and the light coupling enhancement with the TiO2 scattering medium. Core-shell TiO2@Silica with an appropriate silica shell (thickness and homogeneity) allowed to obtain a colloidal suspension with a significantly high scattering strength. Studies in progress in this strongly scattering media have demonstrated the partial confinement of light ("localization transition"), which represents the confirmation of one of the most interesting phenomena of many bondies physics (highly disordered means) called Anderson Localization.